2016
DOI: 10.1080/09273972.2016.1242640
|View full text |Cite
|
Sign up to set email alerts
|

Symptoms in Children with Intermittent Exotropia and Their Impact on Health-Related Quality of Life

Abstract: Purpose In childhood intermittent XT the frequency and type of symptoms has not been rigorously studied. We aimed to identify specific symptoms in children with intermittent XT, their frequency, and effects on health-related quality of life (HRQOL). Methods 35 children (5–13 years) with intermittent XT, without previous surgery were enrolled in a prospective cohort study. Specific symptoms were identified from a previous study involving child and parent interviews and formulated as a 22-item symptom question… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
30
2
1

Year Published

2020
2020
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(38 citation statements)
references
References 23 publications
0
30
2
1
Order By: Relevance
“…In general, the more severe the IXT, the worse the HRQOL. However, Hatt and Lim [9,10] found that while parents' HRQOL was related to the children's IXT severity, no such relationship was present in the children. In this way, the clinical ndings of IXT in these children do not fully correspond with their mental health.…”
Section: Introductionmentioning
confidence: 97%
“…In general, the more severe the IXT, the worse the HRQOL. However, Hatt and Lim [9,10] found that while parents' HRQOL was related to the children's IXT severity, no such relationship was present in the children. In this way, the clinical ndings of IXT in these children do not fully correspond with their mental health.…”
Section: Introductionmentioning
confidence: 97%
“…Findings include one or either eye deviating outward some of the time, diplopia, headaches, photophobia/photalgia, closing or winking of one or either eye, or reduced binocular visual acuity [ 5 , 6 , 7 ]. Clinical assessment for this condition includes visual acuity, binocular functions, prism diopter (pd) measurements, assessments of control, classification of exodeviation and the presence of pattern deviations [ 1 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 ]. Both symptoms and assessment outcomes may be used to determine the need for surgery in this population and are important considerations prior to intervention [ 1 , 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…2,3,6 Symptoms of intermittent exotropia include concerns about cosmesis, 9 intermittent diplopia, tired eyes, excessive blinking and reduced quality of life. 10,11 The management of intermittent exotropia includes both surgical and nonsurgical treatment options (i.e., watchful observation, patching, prisms, over-minus lenses and vision therapy/ orthoptics). [12][13][14][15] In recent years, a number of randomised clinical trials have been performed to study the effectiveness of both surgical 16 and non-surgical 17,18 treatment of intermittent exotropia, and various outcome measures have been used in these studies.…”
Section: Introductionmentioning
confidence: 99%
“…Intermittent exotropia is a common form of strabismus 1–8 with an estimated prevalence of 0.5%–3.3% in children 2,3,6 . Symptoms of intermittent exotropia include concerns about cosmesis, 9 intermittent diplopia, tired eyes, excessive blinking and reduced quality of life 10,11 . The management of intermittent exotropia includes both surgical and non‐surgical treatment options (i.e., watchful observation, patching, prisms, over‐minus lenses and vision therapy/orthoptics) 12–15 …”
Section: Introductionmentioning
confidence: 99%